ANALISIS BUKU : BAGAIMANA KURIKULUM 2013 MEMFASILITASI BERKEMBANGNYA KETERAMPILAN MENGAMATI PADA SISWA KELAS 1,2,4 DAN 5? - Kintan Limiansih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2016)
We analyzed the activities in the student books Curriculum 2013.This research was to understand the development of observation skills in the student book. This research was analyzed student books for grade 1, 2, 4, and 5. From the analysis, obtained information that in the student books have contained instructions or assignments for students to observe objects / events / real phenomenon that results are in keeping with the facts (appearing in grades 1, 2, 4, and 5), use a variety of senses (appearing in grade 1, 2, 4, and 5), determine similarities or differences (appearing in grades 1, 2, 4, and 5), and repeated observations to obtain accurate results (appearing in grade 1 and 4). But in the book there are no clues student or assignment for the students to use the tools of observation so the range of observation and no further details are also instructions for preparing the observation stage. In addition, the activity observed in the students' books are dominated by observing the images so that the information obtained by the students is limited.